A National Overview of Surgical Misadventures in Head and Neck Surgery: “Oh no, you cut it” - Al-Qurayshi, Zaid (Laryngoscope, 2019)
OBJECTIVES: To examine the risk and prevalence of accidental intraoperative injury reported during head and neck surgeries and the associated outcomes. METHODS: A retrospective cross-sectional analysis utilizing the Nationwide Readmissions Database, 2010 – 2014. Adults patients with a reported accidental intraoperative injury were compared to controls without such injuries. RESULTS: A total of 173 cases and 105,659 controls were included. Most cases were reported in surgeries of the mouth/ tonsils (29.4%) and maxillofacial bones/mandible (22.5%). The remaining cases were reported in surgeries of the pharynx/larynx (17.5%), nose/paranasal sinuses (15.4%), salivary glands & ducts (6.2%), thyroid/parathyroid (5.2%), and ear (3.8%). The multivariate logistic regression model demonstrated that surgeries of the pharynx/larynx were associated with the highest risk of injuries compared to other site surgeries [OR: 2.51, 95%CI: (1.49, 4.25), p<0.001]. Concomitant neck dissection was also independently associated with the risk of injury [OR: 4.07, 95%CI: (2.05, 8.09), p<0.001]. Compared to controls, cases were not associated with an increased risk of mortality (p=0.63) or readmission (p=0.29), however, those cases had a significantly longer hospital-stay on average by 3.64±0.95 days/case (p<0.001) and a higher cost of treatment, on average by $13,478±119.42/case (p<0.001). CONCLUSIONS: This study reports on the prevalence and outcomes of accidental intraoperative injuries reported in head and neck surgeries. The prevalence is relatively low, and the annual trend appears stable, however, it is associated with a significant burden on the health system.